Epidemiological trends of mosquito-borne viral diseases in Pakistan - Muhammad Imran; Jing Ye; Muhammad K. Saleemi; Iqra Shaheen; Ali Zohaib; Zheng Chen; Shengbo Cao (BMC, 2022)
Abstract Globally, arboviruses are public health problems. Pakistan has seen a fast-paced increase in mosquito-borne Flavivirus diseases such as dengue because of deforestation, climate change, urbanization, poor sanitation and natural disasters. The magnitude and distribution of these diseases are poorly understood due to the lack of a competitive nationwide surveillance system. In dengue-endemic countries, the recent epidemics of chikungunya (CHIKV) and human West Nile virus (WNV) have created panic among the public and are thought to provoke an outbreak of Zika virus (ZIKV) in Pakistan. Recently, hospital-based surveillance has indicated the presence of Japanese encephalitis virus (JEV), which is deeply concerned by developing countries such as Pakistan. The situation could become more devastating because of poorly developed diagnostic infrastructure. To date, no licensed vaccine has been used in Pakistan, and preventive measures are mainly based on vector control. This review provides comprehensive information concerning the association of risk factors with disease occurrence, epidemiological trends, and prediction of the spread of mosquito-borne diseases, attention to new threats of ZIKV, and future perspectives by benchmarking global health policies.